2021
DOI: 10.1038/s41380-021-01331-7
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal study of a first episode psychosis cohort: potential markers of antipsychotic treatment resistance

Abstract: Treatment resistant (TR) psychosis is considered to be a significant cause of disability and functional impairment. Numerous efforts have been made to identify the clinical predictors of TR. However, the exploration of molecular and biological markers is still at an early stage. To understand the TR condition and identify potential molecular and biological markers, we analyzed demographic information, clinical data, structural brain imaging data, and molecular brain imaging data in 7 Tesla magnetic resonance s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…(2) some individuals from the putative GSH-excess subgroup (or redox sufficient) may still progress to chronic or resistant stages of schizophrenia. In the context of our current observation of increased variation in GSH levels in schizophrenia, the extant literature supports the model of 'Primary GSH Deficit' (Figure 2) in some individuals with schizophrenia; this deficit may be pathoplastic and influence the treatment outcomes [e.g., treatment resistance (47)] among patients. Demonstrating bimodal distribution of GSH levels in large samples of patients in early illness stages, in conjunction with clinical and functional validation of the distributed values, will add substantial evidence to our claim regarding the existence of subgroups (16).…”
Section: Discussionsupporting
confidence: 76%
“…(2) some individuals from the putative GSH-excess subgroup (or redox sufficient) may still progress to chronic or resistant stages of schizophrenia. In the context of our current observation of increased variation in GSH levels in schizophrenia, the extant literature supports the model of 'Primary GSH Deficit' (Figure 2) in some individuals with schizophrenia; this deficit may be pathoplastic and influence the treatment outcomes [e.g., treatment resistance (47)] among patients. Demonstrating bimodal distribution of GSH levels in large samples of patients in early illness stages, in conjunction with clinical and functional validation of the distributed values, will add substantial evidence to our claim regarding the existence of subgroups (16).…”
Section: Discussionsupporting
confidence: 76%
“…The group led by Akira Sawa utilized a multimodal longitudinal cohort to investigate biomarkers for treatment-resistant psychosis. Their study observed reductions in hippocampal volumes and glutathione (GSH) levels in the anterior cingulate cortex in treatment resistent patients compared to responsive patients ( Yang et al, 2022 ). Interestingly, they found that a combination of multimodal biomarkers could lead to a better prediction of treatment resistance than any individual biomarker.…”
Section: Imagingmentioning
confidence: 99%
“…Prediction of antipsychotic response in schizophrenia is slowly moving from clinical and socio-demographic towards biological markers such as inflammation and resting state functional connectivity ( Enache et al, 2021 ; Mehta et al, 2021 ; Mongan et al, 2020 ; Yang et al, 2021 ). This is a first step towards identifying disease-biology-based predictive biomarkers that can subsequently help in (a) the early identification and treatment of resistant schizophrenia, (b) treatment planning and resource allocation, and (c) delivering personalized treatments ( Kraguljac et al, 2021 ).…”
Section: Newer Agents and Treatment Optimizationmentioning
confidence: 99%